THE ANALYSIS OF ROLE-PLAY TECHNIQUE IN TEACHING SPEAKING AT GRADE 11th IN SMKN 6 MEDAN - Ria Natasha Graycella Simanjuntak; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2022)
The aim of this study was to discover how the role-play technique is implemented in the teaching learning English at grade 11th of SMKN 6 Medan. The methodology of this study is descriptive qualitative research. The researcher took one class in 11th grade for Marketing major. The researcher used observational tally sheet and video recording as the instruments for collecting the data. The data were analyzed by using Porter-Ladousse’ Role-Play Technique and Diane Freeman’ Review of Technique. The teacher implemented the role-play technique well; it can be seen from all stages procedure conducted by the teacher during teaching learning process. He did almost all stages that asked role-play technique by Porter Ladouse’s theory and teaching technique review by Diane Freeman’s theory. The researcher found that the teacher implemented to role-play technique by the proper technique following Porter Ladousse theory and Diane Freeman theory. Even though this time is currently a pandemic period and there are restrictions on face-to-face learning, the teacher can still apply role-playing techniques well, even though some things are lacking, such as follow-ups fill-in-the-blanks exercises and map drawing at grade XI of SMKN 6 Medan.Keywords: Role-Play, Teaching Technique, Review Technique